(untitled) (Research, Society and Development, 2023)
The sound systems are mega-structures of electronic equipment used to liven up the parties held mainly on the outskirts of Belém, in the state of Pará, Brazil, being recognized as a cultural element, typical of this region and are mostly attended by young who are in the age group of 15 to 29 years old. The aim was to investigate the relationships established by young people during their leisure practices with the “Gigante Crocodilo Prime” sound system of Belém do Pará. The methodology has based on the qualitative approach and consisted of observing the leisure experience of young people in the context of sound system parties, and the data were analyzed by means of the content analysis technique, with the support of the NVivo software. It has been concluded that young people attend the sound system parties to develop a lifestyle taken by technology. Thus, the success and the effervescence of the sound system parties within the context of the outskirts of the city occur due to the development process of the parties themselves, which make their regulars being taken by a sort of sound frenzy that make them feel as if their bodies were being summoned to such venues.